Lowest-unmatched price auctions - Eichberger, Jürgen; Vinogradov, Dmitri V. (International journal of industrial organization, 2015)
Lowest-Unmatched Price Auctions (LUPAs) specify that the lowest bid placed by only one participant wins. They are used in internet trading and TV and radio shows. We model LUPAs as games with minimal restrictions, in particular allowing players to place more than one bid, since multiple bids have been observed in most actual LUPAs. Though LUPAs are games for which a closed-form solution does not seem to exist in general, our model generates several testable implications about the type of strategies played in equilibrium and the highest bid in a given LUPA. Our analysis suggests that players follow strategic considerations and arrive at decisions which, at least in the aggregate, are generally consistent with theoretical predictions, yet there are some remarkable deviations.